First cytogenetic characterization of the giant Amazonian catfish Brachyplatystoma filamentosum (Siluriformes, Pimelodidae) - Martini Goncalves, Alvaro Luiz [UNESP]; Prado, Fernanda Dotti do [UNESP]; Ferreira, Daniela Cristina [UNESP]; Voltolin, Tatiana Aparecida [UNESP]; Senhorini, Jose Augusto; Foresti, Fausto [UNESP]; Porto-Foresti, Fabio [UNESP] (Univ Florence Botany Inst, 2014)
In contrast to the enormous variability of Neotropical fish species, genetic information about many groups is not yet available. Chromosomal studies have greatly contributed to the characterization of several species, providing important data on these animals. We performed the first cytogenetic characterization of the Amazonian fish species Brachyplatystoma filamentosum (Pimelodidae), popularly known as "piraiba". The results revealed a diploid number of 2n = 56 composed of 24 metacentric, 12 submetacentric, and 10 acrocentric chromosomes in both females and males. After silver nitrate treatment (AgNORs) it was possible to visualize the nucleolus organizer region located in the terminal portion of the short arms of subtelocentric chromosome pair 22, presenting size polymorphism. Hybridization with 18S and 5S rDNA probes confirmed the number and location of 18S marks rDNA in pair 22 and differences in the size of signals among homologs. The 5S rDNA genes were localized near the centromere on the short arms of chromosome pair 19. Constitutive heterochromatin (C-bands) were localized predominantly in the terminal regions of the chromosomes, and also occurred in some interstitial and centromeric positions. The chromosomal genetic data obtained in this study contribute to the biological characterization of B. filamentosum, which has economic and ecological importance as the largest freshwater catfish occurring in many rivers of the Amazon and Tocantins-Araguaia basins in Brazil. These results may also be used in to infer relationships among Pimelodidae species.
Keywords: Neotropical fish; chromosome; NOR; 18S rDNA; 5S rDNA